The fears of judgement effect a question wording effect due to hypothesis confirmation bias - Lehman, Darwin R.; Krosnick, Jon A.; West, Robert L.; Fan,Li (1992)
Three sstudies whether the focus of judgement of a rating scale question can influence responses through a hypothesis confirmation bias. Study 1 showed that focusing the question wording on one of two political parties led non-partisan subjects who had little relevant knowledge to evaluate media coverage as more hostile to that party. Studies 2 and 3 demonstrated that asking for the likelihood that the person was a lawyer. This effect occurred only when a large amount of hypothesis compatible information was available to subjects when they paid close attention to it, and when they had previously been successful t interpreting information as consistent with the hypothesis implied by the question. Together, these studies illustrate two focus of judgement effects and identify factors that regulate their magnitude.